Fetal Outcomes with Detoxification from Opioid Drugs during Pregnancy: A Systematic Review - Towers, Craig V.; Terry, Paul; Rackley, Breanne; Hennessy, Mark; Visconti, Kevin (American Journal of Perinatology, 2020)
Objective This study aimed to perform a systematic review of all studies reporting fetal outcomes following detoxification or tapering of opioid drugs during pregnancy.Study Design PubMed, Scopus, Medline, and Google Scholar were searched, and only manuscripts clearly reporting pregnancy/fetal outcomes involving tapering or detoxification from opioid drugs were included. Only pregnancies managed after 1980 were included (when antenatal fetal surveillance became more routine). Collected data included study design, location, years patients were managed, number of patients who were tapered or detoxified, method of tapering, and pregnancy outcome.Results A total of 14 publications met the criteria for review after evaluating more than 2,000 abstracts and 153 published manuscripts. In 1,097 pregnancies, based on mortality rate analyses and forest plots, no increased fetal risks due to tapering or detoxification from opioid drugs were identified. No increased risk of preterm delivery was found.Conclusion Pregnant women with opioid use disorder who are stable in a medication-assisted treatment program with behavioral health can be informed that tapering or full detoxification from opioid drugs does not increase the fetal risk of poor pregnancy outcome. Future research needs to answer the questions on maternal and long-term newborn consequences of tapering or detoxification versus long-term newborn consequences of continued chronic in utero opioid exposure.
Keywords: opioid use disorder; substance abuse; drug abuse; neonatal abstinence syndrome; overdose; methadone; buprenorphine; naltrexone; heroin